CASP9 (caspase 9) is essential for autophagosome maturation through regulation of mitochondrial homeostasis. Issue 9 (1st September 2020) - An, Hyun-Kyu; Chung, Kyung Min; Park, Hyunhee; Hong, Jihyun; Gim, Ji-Eun; Choi, Hyosun; Lee, Ye Won; Choi, Jieun; Mun, Ji Young; Yu, Seong-Woon
ABSTRACT: CASP9 (caspase 9) is a well-known initiator caspase which triggers intrinsic apoptosis. Recent studies also suggest various non-apoptotic roles of CASP9, including macroautophagy/autophagy regulation. However, the involvement of CASP9 in autophagy and its molecular mechanisms are not well understood. Here we report the non-apoptotic function of CASP9 in positive regulation of autophagy through maintenance of mitochondrial homeostasis. Growth factor or amino acid deprivation-induced autophagy activated CASP9, but without apoptotic features. Pharmacological inhibition or genetic ablation of CASP9 decreased autophagy flux, while ectopic expression of CASP9 rescued autophagy defects. In CASP9 knockout (KO) cells, initiation and elongation of phagophore membranes were normal, but sealing of the membranes and autophagosome maturation were impaired, and the lifetime of autophagosomes was prolonged. Ablation of CASP9 caused an accumulation of inactive ATG3 and decreased lipidation of the Atg8-family members, most severely that of GABARAPL1. Moreover, it resulted in abnormal mitochondrial morphology with depolarization of the membrane potential, reduced reactive oxygen species production, and aberrant accumulation of mitochondrial fusion-fission proteins. CASP9 expression or exogenously added H2 O2 in the CASP9 KO cells corrected the ATG3 level and lipidation status of Atg8-family members, and restored autophagy flux. Of note, only CASP9 expression but not H2 O2 rescued mitochondrial defects, revealing regulation of mitochondrial homeostasis by CASP9. Our findings suggest a new regulatory link between mitochondria and autophagy through CASP9 activity, especially for the proper operation of the Atg8-family conjugation system and autophagosome closure and maturation. Abbreviations: AA: amino acid; ACD: autophagic cell death; ACTB: actin beta; ANXA5: annexin A5; APAF1: apoptotic peptidase activating factor 1; Atg: autophagy related; ATG16L1: autophagy related 16 like 1; BafA1 : bafilomycin A1 ; BCL2: BCL2 apoptosis regulator; BECN1: beclin 1; CARD: caspase recruitment domain containing; CASP: caspase; CM-H2 DCFDA: chloromethyl-2ʹ, 7ʹ-dichlorodihydrofluorescein diacetate; Δψm: mitochondrial membrane potential; DN: dominant-negative; DNM1L/DRP1: dynamin 1 like; EBSS: Earle's balanced salt solution; GABARAP: GABA type A receptor-associated protein; GABARAPL1: GABA type A receptor associated protein like 1; GABARAPL2: GABA type A receptor associated protein like 2; HCN: hippocampal neural stem cells; IAM: inner autophagosome membrane; INS: insulin; KO: knockout; LEHD: Z-LEHD-fmk; MAP1LC3: microtubule associated protein 1 light chain 3; MFN1: mitofusin 1; MFN2: mitofusin 2; MTORC1: mechanistic target of rapamycin kinase complex 1; PARP1: poly(ADP-ribose) polymerase 1; PBS: phosphate-buffered saline; PE: phosphatidylethanolamine; ROS: reactive oxygen species; sgRNA: single guide RNA; SR-SIM: super-resolution structured illumination microscopy; SQSTM1: sequestosome 1; STS: staurosporine; STX17: syntaxin 17; TMRE: tetramethylrhodamine ethyl ester; TUBB: tubulin beta class I; ULK1: unc-51 like autophagy activating kinase 1; WT: wild type; ZFYVE1/DFCP1: zinc finger FYVE-type containing 1